An Experiment of Hybrid Microfiltration Membranes (MFM) Using Dead-End-Flow Method on Water Source - Subagia, I.D.G. Ary; Kusuma K, Cok Istri Putri (Journal of Materials Engineering and Processing Technology; Vol 1 No 01 (2017): JOURNAL OF MATERIAL SCIENCE AND PROCESSING TECHNOLOGY (JMSPT), 2017)
The focus of this experiment is to investigate advisability of hybrid microfiltration membrane against natural water qualities. Hybrid membrane microfilter (MF) was produced through casting method. Moringa olifera powder mixed with activated carbon of coconut shell charcoal powder were used as reinforcement and biopolymer ceresin and polyvinyl alcohol (PVA) used as composite matrix. In order to testing hybrid MF membrane of turbidity of water the method of Dead-End-Flow (DEF) was carried out. The main purpose is to investigate the turbidity and swelling of hybrid MF membrane after water filtration. The experiment result shows moringa oleifera as an organic has good function to reduce water pollutant like bacteria. Then, activated carbon of coconut shell charcoal own has unique characteristic in water treatment are eliminate the water color, odor, toxin absorb and chemicals. In addition, hybrid MF membrane with moringa oleifera/activated carbon coconut shell charcoal/PVA/ceresin has been impacted against to turbidity value of water sources. Then swelling of hybrid MF membrane was increased with increasing member of moringa oleifera in specimen. It can be concluded that hybrid MF membrane is an alternative for water purification.   Key words; Hybrid, Membrane, Microfiltration, Dead end flow, Turbidity.